Prediction‐based picture prioritisation method for hierarchical B‐structure of high efficiency video coding. Issue 20 (1st September 2013) - Ryu, E.‐S.
Abstract : The current high efficiency video coding standard does not provide any syntax for prioritising pictures in the same temporal level of hierarchical structure. Thus, this reported work reveals how the current uniform prioritisation method in hierarchical B pictures can cause severe video quality degradation when video packets are transmitted over error‐prone channels. To solve this problem, a new picture prioritisation method using prediction information is proposed.